Prevalence of Venous Thromboembolism in Hip and Knee Arthroplasty Patients Admitted for Comprehensive Inpatient Rehabilitation - Gregory, Patricia C.; Lennox, Dennis; Kuhlemeier, Keith V.; Bennett, Errol; Czajkowski, Dorothy (Vascular Disease Prevention (Discontinued), 2005)
Introduction: Venous thromboembolism (DVT) is a prevalent, potentially fatal complication following orthopedic joint replacement of the lower extremity. Diagnosis is difficult because DVT symptoms are similar to the post operative sequelae. Prophylaxis treatment often varies based upon surgeon's preference. We determined the prevalence and factors associated with DVT in a cohort of total joint arthroplasty (TJA) patients admitted for comprehensive inpatient rehabilitation (CIR). Methods: Patient's admitted for CIR following TJA from 1995-1999 were retrospectively reviewed. All patients were screened within 48 hours of admission to CIR. The prevalence of DVT during the study period was calculated. Data collected on the co morbid medical conditions, type of surgery, anesthesia, complications, DVT prophylaxis therapy, and demographic variables were entered into a multiple logistic regression analysis to evaluate their association with DVT. Results: One-hundred eighty-one patients were included in the study. DVT prevalence was 19.3% (35/181). Pulmonary embolus (PE) rate was low at 0.6% (1/181). None of the associated variables reached statistical significance. Discussion: Although type of DVT prophylaxis was not predictive of DVT risk, the small sample size may explain the negative finding. The low prevalence rate of PE was attributed to the study design of screening patients on admission leading to early discovery and treatment of DVT which effectively lowered the risk of PE. The prevalence of DVT emphasizes the need for appropriate DVT prophylaxis in this at risk population.
Keywords: prevalence